2017
DOI: 10.3389/fpls.2016.01979
|View full text |Cite
|
Sign up to set email alerts
|

A Grapevine TTG2-Like WRKY Transcription Factor Is Involved in Regulating Vacuolar Transport and Flavonoid Biosynthesis

Abstract: A small set of TTG2-like homolog proteins from different species belonging to the WRKY family of transcription factors were shown to share a similar mechanism of action and to control partially conserved biochemical/developmental processes in their native species. In particular, by activating P-ATPases residing on the tonoplast, PH3 from Petunia hybrida promotes vacuolar acidification in petal epidermal cells whereas TTG2 from Arabidopsis thaliana enables the accumulation of proanthocyanidins in the seed coat.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 89 publications
(166 reference statements)
2
80
0
Order By: Relevance
“…Expression profiles of VvMYB5a and VvMYB5b (Cavallini et al ., ) have been compared with that of VvWRKY26 , which is the homologue of PhPH3 and AtTTG2 and encodes a WRKY transcription factor that can replace the function of PH3 in transgenic ph3 petunia plants (Amato et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Expression profiles of VvMYB5a and VvMYB5b (Cavallini et al ., ) have been compared with that of VvWRKY26 , which is the homologue of PhPH3 and AtTTG2 and encodes a WRKY transcription factor that can replace the function of PH3 in transgenic ph3 petunia plants (Amato et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…We recently demonstrated that VvWRKY26, the apparent homologue of AtTTG2 and PhPH3 (Wang et al ., ; Verweij et al ., ), can replace the function of the endogenous PH3 in petunia flowers (Amato et al ., ). Expression of VvWRKY26 in ph3 flowers restores the pH of crude petal limb extracts, the colour of the corolla and the wild‐type expression levels for PhPH1 and PhPH5 in petals.…”
Section: Introductionmentioning
confidence: 97%
“…The Arabidopsis TT8 protein groups in a distinct clade (Consonni, Geuna, Gavazzi, & Tonelli, 1993;Hernandez, Feller, Morohashi, Frame, & Grotewold, 2007) together with the petunia AN1 (Spelt, Quattrocchio, Mol, & Koes, 2000) and the maize IN factor (Burr et al, 1996). The WRKY factor is encoded by a single gene in all studied species (Amato et al, 2017;Johnson, Kolevski, & Smyth, 2002;Verweij et al, 2016). All components of the WMBW complex are essential to efficiently activate anthocyanin synthesis, as shown by the loss (or reduction) of pigmentation in mutants for each of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…With the release of an increasing number of genome sequences, more and more WRKY genes 51 have been identified in a wide range of plant species [9][10][11][12][13][14], suggesting that WRKY proteins have 52 evolved diverse functions with different biochemical properties. To date, many plant WRKY 53 proteins have also been functionally studied in detail, suggesting that they are implicated to 54 modulate seed development, flowering, fruit ripening, senescence and various metabolic processes 55 by binding to W-box element ((C/T)TGAC(T/C)) in the promoter of downstream target genes 56 [15][16][17][18][19]. For example, a WRKY protein is strongly expressed in the endothelium of 57 developing seeds, and plays important role during seed coat development in Arabidopsis [20].…”
mentioning
confidence: 99%